Enhancing the toughness of talc filled polypropylene - the application of ethylene propylene rubber as impact modifier - Mohd Hasbullah, Mohd Hasbullah; Hassan, Azman (Jabatan Kimia, Universiti Teknologi Malaysia, 2005)
Polypropylene (PP) is a popular plastics material which is being used for injection moulding and extrusion applications. Fillers such as talc are being incorporated into PP to reduce cost and also to improve certain properties such as stiffness. However the addition of talc causes a reduction in toughness resulting in relatively brittle materials. Improvements in impact strength of talc filled polypropylene can be sought by melt blending with impact modifiers such as ethylene-propylene rubber (EPR). In this study, blends of talc filled PP and EPR were prepared in a laboratory scale extruder. The concentration of EPR was varied from 10 - 25 phr with an increment of 5 phr. After pelletising, the PP compounds were injection moulded and tested for mechanical properties. Mechanical tests such as impact, tensile and flexural were conducted to investigate the effects of EPR on mechanical properties of talc filled PP. The results show that the additions of EPR in talc filled PP decreased the Young's modulus, tensile strength, flexural modulus and flexural strength. However, EPR is found to be an effective impact modifier for talc filled PP. The optimum content of EPR in talc filled PP which gives balance of mechanical properties in terms of stiffness and toughness was found to be between 16 to 18 phr.